Portada - -, - (Alteridades, 2017)
This number of Alteridades illustrate the concurrence in the studies of the performance of disciplines, intellectual and theoretical traditions, with whom dialogues and debates to erect analytical horizons, social and artistic innovative practices, Fruitful, and socially committed